Matching Biological Mesh and Negative Pressure Wound Therapy in Reconstructing an Open Abdomen Defect - Fabio Caviggioli; Francesco Maria Klinger; Andrea Lisa; Luca Maione; Davide Forcellini; Valeriano Vinci; Luca Codolini; Marco Klinger (Case Reports in Medicine)
Reconstruction of open abdominal defects is a clinical problem which general and plastic surgeons have to address in cooperation. We report the case of a 66-year-old man who presented an abdominal dehiscence after multiple laparotomies for a sigmoid-rectal adenocarcinoma that infiltrated into the abdominal wall, subsequently complicated by peritonitis and enteric fistula. A cutaneous dehiscence and an incontinent abdominal wall resulted after the last surgery. The abdominal wall was reconstructed using a biological porcine cross-linked mesh Permacol (Covidien Inc., Norwalk, CT). Negative Pressure Wound Therapy (NPWT), instead, was used on the mesh in order to reduce wound dimensions, promote granulation tissue formation, and obtain secondary closure of cutaneous dehiscence which was finally achieved with a split-thickness skin graft. Biological mesh behaved like a scaffold for the granulation tissue that was stimulated by the negative pressure. The biological mesh was rapidly integrated in the abdominal wall restoring abdominal wall continence, while the small dehiscence, still present in the central area, was subsequently covered with a split-thickness skin graft. The combination of these different procedures led us to solve this complicated case obtaining complete wound closure after less than 2 months.